ANALISIS PENGARUH KUALITAS PELAYANAN, KOMITMEN, DAN KEPERCAYAAN NASABAH TERHADAP KEPUASAN DAN LOYALITAS NASABAH PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK AREA MAKASSAR RAYA - Farina Fakhruddin; Haris Maupa; Muhammad Ismail (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2018)
Currently the development of banking services is growing so rapidly because banking is one part of financial institutions that play a very important role for the smooth economic activities of a country. This study aims to determine and analyze the influence of Service Quality, Commitment, and Customer Confidence Against Customer Satisfaction And Loyalty At PT. Bank Rakyat Indonesia (Persero) Tbk Makassar Area Raya. The type of research used in this study is quantitative approach. The quantitative approach bases the study of empirical rational principles. The quantitative approach bases the study of empirical rational principles. Therefore, before doing research the researcher must find the problem and hypothesis to be tested based on the criteria specified and the analytical tool used is Smart PLS 2.0. The results showed that partially, the quality of service, commitment, and customer confidence have a positive and significant impact on satisfaction. Furthermore, service quality variables, commitment, customer trust and satisfaction have a positive and significant effect on customer loyalty. The indirect effect indicates that satisfaction can mediate the influence of service quality, commitment, and trust of customer to customer loyalty of PT. Bank Rakyat Indonesia (Persero) Tbk Makassar Area Raya positively and significantly.